Kurikulum Merdeka dan Pengaruhnya pada Perkembangan Moral Anak SD : Sebuah Kajian Literatur - Chairul Azmi; Irda Murni; Desyandri Desyandri (Departement of Mathematics Education, 2023)
The Merdeka Curriculum can play an important role in the moral development of students. By giving students the freedom to manage the course of learning, this curriculum encourages students to become individuals who are responsible for their own learning. In the process, students can be invited to consider the moral consequences of the actions and decisions they take. They can learn to understand the impact of their actions on themselves, others, and the environment. The purpose of writing this article is to provide information about the independent curriculum and its influence on the moral development of elementary school children. The writing method is a literature review taken from various articles related to the discussion. Through a literature review, it was found that in the implementation of an independent curriculum, they can develop a wider moral awareness and become responsible and moral members of society.